Cardiorespiratory alterations following intermittent photostimulation of RVLM C1 neurons: Implications for long‐term blood pressure, breathing and sleep regulation in freely moving rats. (20th August 2022) - Toledo, Camilo; Andrade, David C.; Diaz‐Jara, Esteban; Ortolani, Domiziana; Bernal‐Santander, Ignacio; Schwarz, Karla G.; Ortiz, Fernando C.; Marcus, Noah J.; Oliveira, Luiz M.; Takakura, Ana C.; Moreira, Thiago S.; Del Rio, Rodrigo
Abstract: Aim: Sympathoexcitation and sleep‐disordered breathing are common contributors for disease progression. Catecholaminergic neurons from the rostral ventrolateral medulla (RVLM‐C1) modulate sympathetic outflow and have anatomical projections to respiratory neurons; however, the contribution of highly selective activation of RVLM‐C1 neurons on long‐term autonomic and breathing (dys)regulation remains to be understood. Methods: To explore this relationship, a lentiviral vector carrying the light‐sensitive cation channel channelrhodopsin‐2 (LVV‐PRSX8‐ChR2‐YFP) was unilaterally injected into the RVLM of healthy rats. On the contralateral side, LVV‐PRSX8‐ChR2‐YFP was co‐injected with a specific immunotoxin (DβH‐SAP) targeted to eliminate C1 neurons. Results: Intermittent photostimulation of RVLM‐C1 in vivo, in unrestrained freely moving rats, elicited long‐term facilitation of the sympathetic drive, a rise in blood pressure and sympatho‐respiratory coupling. In addition, photoactivation of RVLM‐C1 induced long‐lasting ventilatory instability, characterized by oscillations in tidal volume and increased breathing variability, but only during non‐rapid eye movement sleep. These effects were not observed when photostimulation of the RVLM was performed in the presence of DβH‐SAP toxin. Conclusions: The finding that intermittent activation of RVLM‐C1 neurons induces autonomic and breathing dysfunction suggest that episodic stimulation of RVLM‐C1 may serve as a pathological substrate for the long‐term development of cardiorespiratory disorders.